Indira’s story - Dawe, Russell Eric (Revue canadienne de l’éducation médicale, 2017)
Indira is an independent woman who does not live a traditional Nepali life. She rescues abandoned and abused young women from sexual exploitation and provides them with love, support, and education. Her story highlights the key role of the social determinants of health in caring for marginalized populations. Challenges and benefits of attempting to learn from another’s personal narrative are also considered.